The influence of media multitasking on the impulse to buy: A moderated mediation model. (May 2017) - Chang, Yuhmiin
Abstract: This study explores whether and why media multitasking is related to the impulse to buy among young people. The results of an online survey of 993 college students supported the proposed moderated mediation model. For individuals with a higher impulse-buying tendency, media multitasking enhanced the buying impulse through the mediation of high perceived information utility. For individuals with a lower or moderate impulse-buying tendency, media multitasking enhanced the buying impulse through the mediation of high perceived information utility and social presence. The moderated mediation model extended the stimulus-organism- response (S-O-R) framework and demonstrated the moderating influence of an impulse-buying tendency. Highlights: Perceived information utility mediates media multitasking and the impulse to buy. Perceived social presence mediates media multitasking and the impulse to buy. IBT moderates the mediation effect of perceived social presence.